KARAKTERISTIK PERSONAL AUDITOR SEBAGAI ANTESEDEN PERILAKU DISFUNGSIONAL AUDITOR DAN PENGARUHNYA TERHADAP KUALITAS HASIL AUDIT - Ida Oktariani Br Surbakti; Anik Malikah; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThis study aims to determine the auditors personal characteristics of that includelocus of control, turnover intention and employee performance againstdysfunctional behavior of auditors and how the effect on audit quality. Thepopulation of this study are auditor auditors who work at Public Accounting Firm(KAP) Malang registered in OJK issued by Indonesian Institute of CertifiedPublic Accountant (IAPI), both auditors at junior, senior, manager, and / orpartner level. The research used purposive sampling method with 42 respondents.Analytical techniques use path analysis to test the effect of these variables. Theresults showed that the locus of control, turnover intention and employeeperformance simultaneously had a significant effect on auditor dysfunctionalbehavior. Partial testing Locus of control has a positive and significant effect.While Turnover intention and Employee Performance have negative andinsignificant effect to dysfunctional behavior of audit. Dysfunctional behavior andLocus of control partially negatively affect audit quality.Key words :auditor personal characteristic, auditor dysfunctional behavior,audit quality